SERO PREVALENCE OF RUBELLA AMONG UNVACCINATED CHILDREN - SHANTHI RAMESH; KURALARASI PRIYADARSHINI; SHANTHI RAMESH; JAGDEEP RAMESH; D. VIJAYASEKARAN (International Journal of Pharma and Bio Sciences, 2014)
To estimate the sero prevalence of rubella among children attending a tertiary care hospital, in the age group of 1 to 14 years who have not received MMR vaccine.This was a hospital based prospective descriptive study. Blood samples were collected from 50 children aged 1-14 years and analyzed for IgG antibody titres for rubella infection by a quantitative enzyme-linked immunosorbent assay. Data on the socio epidemiological factors was obtained from the parents. The overall rubella sero positivity rate was 58%. The sero positivity increased with age; which was 33% among 1 to 5 years, 55% among 6 to 10 years and 89% among 10 to 14 years. (P=0.01). The study provides information on the increasing sero prevalence of rubella with increasing age among unimmunized children. Since there is an overall sero positivity of only 58% among children, rubella containing vaccine should be included in the National Immunization Schedule to reduce the rubella burden.